2009
DOI: 10.1073/pnas.0811268106
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast protein targeting involves localized translation in Chlamydomonas

Abstract: The compartmentalization of eukaryotic cells requires that newly synthesized proteins be targeted to the compartments in which they function. In chloroplasts, a few thousand proteins function in photosynthesis, expression of the chloroplast genome, and other processes. Most chloroplast proteins are synthesized in the cytoplasm, imported, and then targeted to a specific chloroplast compartment. The remainder are encoded by the chloroplast genome, synthesized within the organelle, and targeted by mechanisms that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
68
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 47 publications
(51 reference statements)
5
68
0
Order By: Relevance
“…The effect of light on the relocalization of the TIC and TOC import machinery to lobe junctions might be relevant to the light stimulation of chloroplast protein import which has been observed in C. reinhardtii and vascular plants (24,30). Moreover, the Rubisco holoenzyme might be assembled in the pathways described here because its small subunit is imported via the TOC and TIC pathway and the chloroplast mRNA encoding the large subunit localizes in situ in the T-zone and is translated in association with membrane (7,31,32). Our findings build upon growing evidence of complex cytological organizations of biogenic processes in organelles and bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The effect of light on the relocalization of the TIC and TOC import machinery to lobe junctions might be relevant to the light stimulation of chloroplast protein import which has been observed in C. reinhardtii and vascular plants (24,30). Moreover, the Rubisco holoenzyme might be assembled in the pathways described here because its small subunit is imported via the TOC and TIC pathway and the chloroplast mRNA encoding the large subunit localizes in situ in the T-zone and is translated in association with membrane (7,31,32). Our findings build upon growing evidence of complex cytological organizations of biogenic processes in organelles and bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…In the Tzone, the CTM is a platform for the synthesis of the plastid genomeencoded subunits. Chloroplast ribosome subunits and PSII subunit mRNAs are recruited to membranes in the T-zone by translation independent mechanisms (e.g., tethering by membrane bound RNA-binding proteins of LDM) (7). The particularly high affinity with which the 30S subunit is bound to the CTM (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pioneering studies demonstrated that some chloroplast ribosomes are attached to the thylakoid membrane by the nascent peptide, implying a cotranslational integration mechanism (8,9). Several specific plastid-encoded proteins have been shown to integrate cotranslationally: the PSII subunits PsbA (also known as D1), PsbB, PsbC, and PsbD; the PSI subunits PsaA and PsaB; and the cytochrome b 6 f subunit PetA (also known as cytochrome f) (10)(11)(12)(13)(14). The insertion of PetA into the membrane requires cpSecA (12,15,16), whereas PsbA integrates independent of both the cpSecA and cpTAT systems (17).…”
mentioning
confidence: 99%